Zinc toxicity response in Ceratoides arborescens and identification of CaMTP, a novel zinc transporter - Li, Xingyue; Zhang, Lin; Ren, Haiyan; Wang, Xiaoyu; Mi, Fugui (Frontiers in Plant Science, 2022)
Zn is an essential micronutrient for several physiological and biochemical processes. Changes in soil Zn levels can negatively affect plant physiology. Although the mechanism of Zn nutrition has been studied extensively in crops and model plants, there has been little research on steppe plants, particularly live in alkaline soils of arid and semiarid regions. Ceratoides arborescens is used in arid and semiarid regions as forage and ecological restoration germplasm, which is studied can enrich the mechanism of Zn nutrition. The plants were exposed to three different Zn treatments, Zn-deficient (-Zn 0 mM L−1), Zn-normal (Control, 0.015 mM L−1), and Zn-excess (+Zn, 0.15 mM L−1), for 3 weeks. Individual biomass, ion concentrations, photosynthetic system, and antioxidant characteristics were measured. High Zn supply significantly decreased plant biomass and induced chlorosis and growth defects and increased Zn concentration but decreased Fe and Ca concentrations, unlike in controls (p<0.05). High Zn supply also reduced plant chlorophyll content, which consequently decreased the photosynthesis rate. Increased concentrations of malondialdehyde and soluble sugar and activities of peroxidase and superoxide dismutase could resist the high-level Zn stress. In contrast, low Zn supply did not affect plant growth performance. We also identified a novel protein through RNA transcriptome analysis, named CaMTP, that complemented the sensitivity of a yeast mutant to excessive Zn, which was found to be localized to the endoplasmic reticulum through transient gene expression in Nicotiana benthamiana. The gene CaMTP identified to be highly sensitive to Zn stress is a potential candidate for overcoming mineral stress in dicot crop plants.